Type 2β Corticotrophin Releasing Factor Receptor Forms a Heteromeric Complex With Dopamine D1 Receptor in Living Cells - Yarur, Hector E.; Andrés, Maria Estela; Gysling, Katia (Frontiers in Pharmacology, 2020)
Corticotrophin releasing factor (CRF) and its related peptides differentially bind to CRF receptors to modulate stress-related behaviors. CRF receptors comprise two G-Protein Coupled Receptors (GPCR), type-1 CRF receptors (CRF1) and type-2 CRF receptors (CRF2). CRF2 encompasses three spliced variants in humans, alpha (CRF2α), beta (CRF2β) and gamma (CRF2γ), which differ in their N-terminal extracellular domains and expression patterns. Previously, we showed that CRF2α form a heteromeric protein complex with dopamine D1 receptors (D1R), leading to changes in the signaling of D1R. Based on the high sequence identity between CRF2α and CRF2β, we hypothetized that CRF2β also heteromerize with D1R. To test the hypothesis, we compared the expression and localization of both CRF2 isoforms and whether CRF2β form stable protein complexes with D1R in HEK293 and ATR75 cell lines. We observed that the immunoreactivity for CRF2β was similar to that of CRF2α in the endoplasmic compartment but significantly higher in the Golgi compartment. Immunoprecipitation analysis showed that CRF2β forms a heteromeric protein complex with D1R. Furthermore, the protein complex formed by CRF2β and D1R was stable enough to change the sub-cellular localization of CRF2β when it was co-expressed with a construct of D1R bearing a nuclear localization signal. Immunofluorescence in A7R5 cells, which endogenously express CRF2β and D1R, shows the colocalization of the CRF2β with D1R and the presence of the heteromer CRF2β/D1R. In conclusion, our results show that CRF2β forms a stable heteromeric protein complex with D1R, a potential new therapeutic target in tissues where both receptors are co-expressed, such as the septum in the brain, and heart, kidney and skeletal muscle in the periphery.